Ecotourism Model in Jakarta - Safitri, Desy; Umasih, Umasih; Ibrahim, Nurzengky; Sujarwo, Sujarwo; Marini, Arita; Wahyudi, Apri (Opción, 2019)
This research aim is to propose ecotourism model in Jakarta. This research used survey method to 1077 tourists in Jakarta in Indonesia using Structur- al Equation Modeling (SEM). The study found that model proposed was good fit for the data. The results confirmed that natural basis, conservation, sustainability, benefit to locals, and awareness were positively associated with ecotourism. Environmental horizon, not destroying environment, loving envi- ronments, and respecting environments have positive relations to natural ba- sis. Guaranteeing benefits of flora and fauna, maintaining environmental har- mony responsibly, using natural environments not excessively, and not writing off tourism place are positively associated with conservation. Preventing nega- tive impact of tourism activities, maintaining environmental balance, natural conservation, and natural sanctuary are positively related to sustainability. Local society welfare, not destroying local culture, financial benefits to society, and local society characters are positively correlated with benefits to locals. Diminishing environmental destruction, not polluting the environments, not using water excessively, and environmental cleanliness are positively associat- ed with awareness. It can be concluded that ecotourism model in this research can be used in Jakarta to protect the environment.